Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

For a geometric random variable X, $P_X(k) = (1-p)^{k-1}p$, then $$E[X] = \sum_{k=1}^{\infty}k(1-p)^{k-1}p\;.$$ That is ($q = 1 -p$) $$E[X] = p + 2qp + 3q^2p + 4q^3p + \dotso $$

But $$P_{X|X>1}(k) = \begin{cases}(1-p)^{k-2}p\text{ if }k > 1\\ 0\text{ if }k = 1\end{cases}$$ $$E[X|X>1] = \sum_{k=2}^{\infty}k(1-p)^{k-2}p\;,$$ that is $$E[X|X>1] + 1 = 1 + 2p + 3qp + 4q^2p + \dotso$$

So how could $E[X|X>1] = E[X] + 1$?

Thanks.

share|improve this question
    
I fixed some things in the formatting. Punctuation after a displayed equation should go inside the dollar signs; else it will appear on the beginning of the next line. And ellipsis (...) in math mode is best produced using \dotso (after/between operators) or \dotsc (after/between commas). –  joriki Aug 30 '11 at 5:45
    
We have $E(X)=p+2qp+3q^2p+\cdots$. Also, $E(X|X>1)=2p+3qp+4q^2p+\cdots$. Both of these use your calculations. Find the second minus the first. You will get an infinite geometric series that has sum $1$. (There are more conceptual ways of seeing the answer, without any calculation.) –  André Nicolas Aug 30 '11 at 5:51
4  
This is the memoryless property of geometric (and exponential) random variables, and can be extended to $E[X|X>n] = E[X|X>0] + n$ for suitable $n$ –  Henry Aug 30 '11 at 7:05
    
Like @Henry said. Furthermore, for every function $u$ and every nonnegative $n$, $E(u(X)\mid X>n)=E(u(X+n))$. –  Did Sep 9 '11 at 13:35
add comment

3 Answers

up vote 6 down vote accepted

Since $P_X(k)$ is normalized, we have

$$\sum_{k=1}^\infty(1-p)^{k-1}p=\sum_{k=2}^\infty(1-p)^{k-2}p=1\;.$$

Thus

$$ \begin{eqnarray} E[X|X>1] &=& \sum_{k=2}^{\infty}k(1-p)^{k-2}p \\ &=& \sum_{k=2}^{\infty}(k-1)(1-p)^{k-2}p+\sum_{k=2}^{\infty}(1-p)^{k-2}p \\ &=& \sum_{k=1}^{\infty}k(1-p)^{k-1}p+1 \\ &=& E[X] + 1 \end{eqnarray} $$

All this is really saying is that since the conditional probability for $k+1$ is the same as the unconditional probability for $k$, the conditional expectation value of $k$ must be the unconditional expectation value of $k+1$.

share|improve this answer
add comment

A coin has probability $p$ of landing heads, and $q=1-p$ of landing tails. Assume that $p\ne 0$.

Let $X$ be the total number of tosses until you get a head. Then $X$ has precisely the geometric distribution that you described. One can, as you did, get an expression for $E(X)$ as an infinite series. In fact, it turns out $E(X)=1/p$. But we need neither the series nor its sum to prove the result that is asked for.

Suppose that we are given that $X>1$. This means that our first toss was a tail. Let $Y$ be the additional number of tosses that we must wait for a head. The coin does not remember that the first toss was a tail, so $Y$ has the same distribution, and therefore the same mean, as $X$. In symbols, $E(Y)=E(X)$.

But the total number of tosses, given that $X>1$, is $1+Y$. The $1$ is for the "wasted" first toss. Thus $$E(X|X>1)=E(1+Y)=1+E(Y)=1+E(X).$$

Comment: If you prove the result using the infinite series, you know that the result is true. If you do it more conceptually, you know why the result is true.

share|improve this answer
    
Great answer! which in addition gives $E[X]$ without needing to sum a series, for we have that $E[X\mid X = 1] = 1$, $E[X \mid X > 1] = 1 + E[X]$, and since the events $\{X = 1\}$ and $\{X > 1\}$ have probabilities $p$ and $1-p$, we get $E[X] = p + (1 + E[X])(1-p) = 1 + (1-p)E[X]$, that is, $E[X] = 1/p$. –  Dilip Sarwate Sep 24 '11 at 2:12
add comment

The "memorylessness" of the geometric distribution implies that the conditional probability distribution of $X$ given that $X\ge\text{any particular integer}$ is the same as the probability distribution of $X+\text{that same integer}$.

share|improve this answer
    
You could have a look at @Henry's comment to the main question. (Additionally, what you write is false since $X\ge1$ almost surely.) –  Did Aug 30 '11 at 14:24
    
Alright, you're starting at 1 rather than 0. So $X+\text{that same integer} - 1$. –  Michael Hardy Aug 30 '11 at 17:21
    
Me? I am not doing anything except reading what the OP wrote. (But what about the first sentence of my previous comment?) –  Did Aug 30 '11 at 17:25
add comment

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.